RAP: A Novel Approach to the Rapid and Highly Sensitive Detection of Respiratory Viruses - Fan, Guohao; Zhang, Ruiqing; He, Xiaozhou; Tian, Fengyu; Nie, Mingzhu; Shen, Xinxin; Ma, Xuejun (Frontiers in Bioengineering and Biotechnology, 2021)
Recombinase aided amplification (RAA) is an emerging isothermal amplification method used for detecting various pathogens. However, RAA requires a complex and long probe to ensure high sensitivity during fluorescence assay. TaqMan probe used for quantitative PCR (qPCR) is simple and universal. Herein, we developed a new approach for detecting nucleic acids of pathogens, known as RAP (Recombinase aided PCR). The method combines RAA and qPCR to ensure a rapid and highly sensitive detection using a conventional qPCR device. RAP is a two-stage amplification process performed in a single tube within one hour. The method involves an RAA reaction for 10 min at 39°C (first stage) followed by 15 cycles of qPCR (second stage). Using human adenovirus 3 (HADV3) and human adenovirus 7 (HADV7) plasmids, the sensitivities of RAP assays for detecting HADV3 and HADV7 were 6 and 17.2 copies per reaction, respectively. The limit of RAP detection was at least 16-fold lower than the corresponding qPCR, and no-cross reaction with other respiratory viruses was observed. The results of RAP analysis revealed 100% consistency with qPCR assay. This study shows that RAP assay is a rapid, specific, and highly sensitive detection method with a potential for clinical and laboratory application.